2021
DOI: 10.1089/g4h.2021.0060
|View full text |Cite
|
Sign up to set email alerts
|

Running App “Zombies, Run!” Users' Engagement with Physical Activity: A Qualitative Study

Abstract: Introduction: Sufficient physical activity is important for all aspects of health. Smartphone apps and the use of gamification, such as narrative-based augmented reality (AR) have a great potential to engage a variety of people in more PA. Zombies, Run! (ZR) is the world's most popular running exergame app and therefore a suitable model to understand what users find engaging.Objective: To understand people's motivation and experience of using a narrative-based AR exergame app ZR for physical activity.Method: Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…provides running scenarios and interactive missions to encourage the players to exercise. Pokémon GO as an exergame uses the number of daily walking steps as rewards to motivate players to engage in exercise and outdoor activities [45,46]. Individuals who have nomophobia may worry if they do not have their smartphone nearby and are unable to monitor or be rewarded for their physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…provides running scenarios and interactive missions to encourage the players to exercise. Pokémon GO as an exergame uses the number of daily walking steps as rewards to motivate players to engage in exercise and outdoor activities [45,46]. Individuals who have nomophobia may worry if they do not have their smartphone nearby and are unable to monitor or be rewarded for their physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Farič et al [ 15 ] and Farič et al [ 16 ] investigated the potential of virtual reality (VR) and narrative-based AR applications. The former found that VR shows promise in engaging adolescents in physical activity, although further development is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Zombies, Run! also had an increase of 2 million users during COVID-19 [ 37 ]. Further, Ellis et al [ 38 ] reported that among 2004 young adult gamers (aged 30.5 years on average), Pokémon Go and Harry Potter: Wizards Unite were played frequently during the pandemic to maintain exercise levels and for social connection.…”
Section: Discussionmentioning
confidence: 99%